2021
DOI: 10.1038/s41598-021-86874-z
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive depletion of Slc34a2/NaPi-IIb in rats causes perinatal mortality

Abstract: Absorption of dietary phosphate (Pi) across intestinal epithelia is a regulated process mediated by transcellular and paracellular pathways. Although hyperphosphatemia is a risk factor for the development of cardiovascular disease, the amount of ingested Pi in a typical Western diet is above physiological needs. While blocking intestinal absorption has been suggested as a therapeutic approach to prevent hyperphosphatemia, a complete picture regarding the identity and regulation of the mechanism(s) responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…BNC2 and PCYT2 are important for the differentiation and maturation of mesenchyme and muscle, respectively, both with origin in the mesodermal germ layer ( Vanhoutteghem et al, 2009 ; Zhu et al, 2009 ). Pcyt2 and Slc39a4 are essential genes for mouse development, as complete knockout mice die during embryogenesis ( Fullerton et al, 2007 ; Pastor-Arroyo et al, 2021 ). Our results reveal that the transcriptional profile of Srrm2 +/− cells is consistent with an altered pluripotent state that affects several development-related genes and is compatible with a mixture of different cellular states within the Srrm2 +/− cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…BNC2 and PCYT2 are important for the differentiation and maturation of mesenchyme and muscle, respectively, both with origin in the mesodermal germ layer ( Vanhoutteghem et al, 2009 ; Zhu et al, 2009 ). Pcyt2 and Slc39a4 are essential genes for mouse development, as complete knockout mice die during embryogenesis ( Fullerton et al, 2007 ; Pastor-Arroyo et al, 2021 ). Our results reveal that the transcriptional profile of Srrm2 +/− cells is consistent with an altered pluripotent state that affects several development-related genes and is compatible with a mixture of different cellular states within the Srrm2 +/− cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that SLC34A2 is widely expressed in multiple organs and plays a critical role in several malignant tumors [14,15]. Depletion of SLC34A2/NaPi-IIb causes perinatal mortality in rats [11]. This finding suggests that SLC34A2 is closely associated with perinatal diseases.…”
Section: Introductionmentioning
confidence: 82%
“…Enhanced availability and absorption of P cause P overload and negatively affect Ca metabolism [10]. Solute carrier (SLC) transporters, the largest family of transmembrane proteins, facilitate the exchange of various substances, including endogenous and xenobiotic compounds, using an electrochemical or ion gradient [11]. Type II Na/Pi co-transporter (NaPi2b), a multitransmembrane sodium-dependent phosphate transporter, is encoded by solute carrier family 34 member 2 (SLC34A2), which is responsible for transcellular inorganic phosphate absorption [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…BNC2 and PCYT2 are important for the differentiation and maturation of mesenchyme and muscle, respectively, both with origin in the mesodermal germ layer (Vanhoutteghem et al, 2009;Zhu et al, 2009). Pcyt2 and Slc39a4 are essential genes for mouse development, as complete knockout mice die during embryogenesis (Fullerton et al, 2007;Pastor-Arroyo et al, 2021). Our results reveal that the transcriptional profile of Srrm2 +/cells is consistent with an altered pluripotent state that affects several development-related genes and is compatible with a mixture of different cellular states within the Srrm2 +/cell cultures.…”
Section: Srrm2 Heterozygous Knockout Shows Specific Splicing Alterationsmentioning
confidence: 99%